Utilization of expander-extruder processed complete diet containing sorghum straw in Ongole bull calves - REDDY, G V N; REDDY, M R (The Indian Journal of Animal Sciences, 2012)
Expander-extruder processed sorghum-straw-based complete diet, corresponding mash diet and a conventional diet (containing concentrate mixture and chopped sorghum-straw) were evaluated in 18 Ongole bull calves (6 in Each group). DMI/100 kg body weight and water intake/kg DMI were similar on all the diets. Digestibilities of DM, OM and CP were significantly (P<0.01) higher on pelleted diet compared to other 2 diets while mash diet recorded higher digestibilities of these nutrients compared to conventional diet. NFE digestibility was significantly (P<0.05) higher on pelleted diet compared to conventional diet. Expander-extruder processing increased the DCP (P<0.01 ) and TDN (P<0.05) contents of the diet. These results indicated that blending of concentrates and roughages into complete diet was beneficial and that processing the mash using expander-extruder markedly improved the nutritive value.